Taking stock of the Regional Foresight Community of Practice in West Africa for a climate resilient region - Segnon, Alcade C.; Obossou, Esdras; Ganyo, Komla Kyky; Kpadonou, G. Esaïe; Lamien, Niéyidouba; Zougmoré, Robert B. (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Given the rapid pace of change, complexity and ambiguity, responsible agricultural policies need to take account of the different possibilities of the future, and foresight analysis provides the means to achieve this. AICCRA through its regional partners, CORAF supported the capacity development of a group of experts on foresight analysis, which resulted in the establishment of a regional community of practice on foresight analysis. The training provided by the foresight experts in the region allowed the CoP members to use foresight analysis tools effectively in their regular work, enabling them to develop a clear vision for any project or initiative within their institution. The effective application of foresight methodology by CoP members is limited by inadequate technical, financial, and institutional support. Achieving successful implementation and scaling of foresight methodology necessitates increased collaboration, partnership, institutional, technical, and financial support.